ANALISIS WACANA KRITIS KAMPANYE VAKSINASI COVID-19 DALAM KOMIK DARING #dukungvaksinitukeren DI INSTAGRAM - Salsabila Salsabila; Tantri Puspita Yazid (Lembaga Pengembangan Kinerja Dosen, 2022)
Problems in handling COVID-19 vaccinations related to receiving and unclear information in the community are a serious matter as well as the reason for the vaccination campaign with a comic strip competition organized by Bank BRI with the hashtag #dukungvaksinitukeren on Instagram. This study aims to find out the discourse on the COVID-19 vaccination campaign by looking at the levels offered by critical discourse analysis in the online comic #dukungvaksinitukeren on Instagram. This research done with qualitative research with Norman Fairclough's critical discourse analysis method. The data collected by using and analizing three online comics #dukungvaksinitukeren which had been selected based on the most likes among the contest participants. The data analysis technique was carried out with three levels of analysis on the micro, meso, and macro structures which were then discussed to see the development of online comic discourse in social media in particular.c #dukungvaksinitukeren covering the microstructural, mesostructural, and macrostructural levels, it shows the use of language, discourse practices, and socio-cultural issues related to the situation during the COVID-19 pandemic and vaccination is displayed in a hyperrealistic way to put forward tho whom striving COVID-19 vaccination in society. It also found how the development of media in the production of online comic discourse is considered the closest medium and an effective form of discourse in instilling power or domination along with its interests.